A model of induction of cerebellar Long-Term Depression including RKIP inactivation of Raf and MEK - Hepburn, Iain; Jain, Anant; Gangal, Himanshu; Yamamoto, Yukio; Tanaka-Yamamoto, Keiko; De Schutter, Erik (Frontiers in Molecular Neuroscience, 2017)
We report an updated stochastic model of cerebellar Long Term Depression (LTD) with improved realism. Firstly, we verify experimentally that dissociation of Raf kinase inhibitor protein (RKIP) from Mitogen-activated protein kinase kinase (MEK) is required for cerebellar LTD and add this interaction to an earlier published model, along with the known requirement of dissociation of RKIP from Raf kinase. We update calcium dynamics as a constant-rate influx, which captures experimental input profiles accurately. We improve AMPA receptor interactions by adding phosphorylation and dephosphorylation of AMPA receptors when bound to glutamate receptor interacting protein (GRIP). The updated model is tuned to reproduce experimental calcium peak vs LTD amplitude curves at 4 different calcium pulse durations as closely as possible. We find that the updated model is generally more robust with these changes, yet we still observe some sensitivity of LTD induction to copy number of the key signaling molecule Protein kinase C (PKC). We predict natural variability in this number by stochastic diffusion may influence the probabilistic LTD response to calcium input in Purkinje cell spines and propose this as an extra source of stochasticity that may be important also in other signaling systems.